ANALISIS DAMPAK KEPERCAYAAN MEREK DAN PERSEPSI KUALITAS PADA PUTUSAN BELANJA MOBIL MEREK TOYOTA - Mashuri, Dian Imami; Palupi, Nur Wulan Intan; Febrima, Achmad Yoki (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
The aim of this study is to investigate the influence of brand trust and perceived quality on the purchasing decisions of consumers who choose Toyota cars. This research uses a population consist-ing of all customers who purchased Toyota cars from official deal-ers located in Kudus, Jepara and Pati Regencies. Researchers took a sample of 97 people from this population. There are two types of data sources used in this research, namely secondary and primary data. By distributing closed questionnaires to respondents, re-searchers will obtain primary data in this research. Meanwhile, secondary data was obtained from relevant sources. The data un-derwent analysis employing the multiple linear regression tech-nique facilitated by the SPSS software. To test the hypothesis, researchers used simultaneous tests, partial tests, and coefficient of determination. The research results show that brand trust and per-ceived quality together have significant and a positive influence on the purchasing decisions of consumers who choose Toyota cars. Separately, the trustworthiness of a brand and the perceived quality of its products play a significant role in shaping choices when making a purchase.